Lumbar bone mineral density in adolescent female runners - Moen, S. M.; Sanborn, C. F.; DiMarco, N. M.; Gench, B.; Bonnick, S. L.; Keizer, H. A.; Menheere, P. P. (The Journal of Sports Medicine and Physical Fitness, 1998)
BACKGROUND: The purpose of this study was to determine if there were significant differences in lumbar bone mineral density (L2-L4, g/cm2) or several hormones among 3 groups of adolescent females: 10 amenorrheic runners, 10 eumenorrheic runners, and 10 eumenorrheic controls. METHODS: Experimental design: comparative. SETTING: Cooper Clinic, Aerobics Center, Dallas, Texas. PATIENTS OR PARTICIPANTS: The subjects were white, non-smokers, aged 15.1-18.8 years, who were not taking birth control pills. All amenorrheic runners had less than 5 menstrual period in the past year, averaging 2,4 periods. The runners averaged approximately 36 miles/week (58.1 km) during the last 9 months of their training season and had been running for 1-5 years. INTERVENTIONS: None. MEASURES: Lumbar bone mineral density (BMD), 10 hormones, percentage of body fat, and dietary intake were measured. RESULTS: Mean lumbar BMD (g/cm2) did not differ significantly among groups (amenorrheic runners = 1.134, eumenorrheic runners = 1.165, controls = 1.148). However, expected trends were observed. Compared to the controls, the amenorrheic runners tended to have lower lumbar BMD and the eumenorrheic runners, higher. Although there were significant differences in concentrations of five serum hormones measured, all mean hormonal values were within normal ranges. Calcium intakes were low for all groups. CONCLUSIONS: In this study, with its small number of subjects and great variability within each group, it was concluded that there is no significant difference among amenorrheic runners, eumenorrheic runners, and controls in lumbar BMD. However, a longer period of amenorrhea might result in significantly lower BMD for the amenorrheic runners.